2004
DOI: 10.1038/sj.gene.6364033
|View full text |Cite
|
Sign up to set email alerts
|

Epistatic effects of genes encoding immunoglobulin GM allotypes and interleukin-6 on the production of autoantibodies to 60- and 65-kDa heat-shock proteins

Abstract: Immunoglobulin GM and KM genes have been associated with antibody responses to a variety of antigens. A promoter-region polymorphism of interleukin-6 (IL-6) gene (À174 G/C) has been shown to be associated with antibody responses to heat-shock proteins (hsp) 60 and hsp65. To examine the possible epistatic effects of these unlinked genetic systems on the autoimmune responses to hsp60 and hsp65, 176 healthy Caucasian subjects from Finland were genotyped for several allelic determinants of GM, KM, and IL-6 genes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Association of non-GM 3 23 5,13 phenotypes with high responsiveness to MUC1 could aid in identifying subjects who are more likely to benefit from MUC1-based vaccines. For individuals with the low responder phenotype, MUC1 could be fused with appropriate adjuvants, such as heat shock proteins, in order to conceive a vaccine that could potentially generate high antibody responses in the majority of population (Li et al, 2006;Pandey et al, 2004). In accordance with Reis CA et al (1998) and Baldus SE at al (1998), our results regarding the survival of patients at 5 years prove the association between the overexpression of MUC1 and the worse prognosis.…”
supporting
confidence: 73%
“…Association of non-GM 3 23 5,13 phenotypes with high responsiveness to MUC1 could aid in identifying subjects who are more likely to benefit from MUC1-based vaccines. For individuals with the low responder phenotype, MUC1 could be fused with appropriate adjuvants, such as heat shock proteins, in order to conceive a vaccine that could potentially generate high antibody responses in the majority of population (Li et al, 2006;Pandey et al, 2004). In accordance with Reis CA et al (1998) and Baldus SE at al (1998), our results regarding the survival of patients at 5 years prove the association between the overexpression of MUC1 and the worse prognosis.…”
supporting
confidence: 73%
“…In addition to infections and overexpression/release of Hsps, other factors, such as genetic predisposition, can also regulate the production of these autoantibodies. Our research group reported that a common genetic polymorphism in the promoter region of the interleukin 6 gene and immunoglobulin GM genotypes affect the production of autoantibodies to Hsp60 and Hsp65 (Veres et al 2002c;Pandey et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This difference indicates essential interpopulation differences and underlines the importance of the aim of the present study. A potential explanation for this difference is based on our recent observation on the epistatic interaction between IL-6 and immunoglobulin genes [23] . Interpopulation differences in the reported Km and Gm allotypes and in other, as yet not identified genes might influence our observations and explain the different behavior of heterozygotes in the two study groups.…”
Section: Discussionmentioning
confidence: 99%